Hubungan Antara Keaktifan Organisasi Dengan Keterampilan Berfikir Kritis Mahasiswa Prodi Bimbingan dan Konseling Universitas Sanata Dharma Yogyakarta: The Relationship Between Organizational Activity and Critical Thinking Skills of Guidance and Counseling Study Program Students at Sanata Dharma University, Yogyakarta - Ninggolan, Elsa Maharani; Antonius Ian Bayu Setiawan (LP3M IAI Al-Qolam, 2025)
This research aims: 1. find out how high the level of student activity is in running an organization, 2. find out how high the level of critical thinking skills of students who are actively involved in organizations, 3. analyze whether there is a significant relationship between organizational activity and critical thinking skills, 4. analyze whether organizational activity can help students develop critical thinking skills. This research method uses aquantutatuve descriptiva correlation approach with the subject of Santa Dharma University’s Guidance and Counseling Study Program students who actively participate in organization totaling 70 students. The data collection technique use a questionnaire using Google Form. The analysis technique uses is validity, reliability, linearity, normality and linear regression hyphotesis tests. The research result is : 1. there is a positive relationship betweem organizational activity and students critical thinking is (R) 0.753 with significance level of 0.000. 2. the level of student organization activity is in the high category with 51% and 46 students. 3. the level of critical thinking skills of students who actively participate in organizations is in the high category with a gain of 53% and 37 students.